Structural Analysis of В4С Bimodal Powder Mixture; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Petukevich М. S; Ivanov Yu. F. Yuriy Fedorovich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Panina A. A. Aleksandra Anatolievna (Chemistry and Physics of Materials, Environmental Materials, 2015)
Title screen